The Determining of Digestible Energy and Digestibility Coefficients of Protein, Calcium and Phosphorus of Malt (Germinated Barley) in Broilers - Moghaddam, Amin Sabet; Mehdipour, Mahdieh; Dastar, Behrouz (International Journal of Poultry Science, 2009)
This experiment was conducted to determinate digestible energy and digestibility coefficients of protein, calcium and phosphorus of malt (germinated barley) and barley in broilers nutrition. Four dietary treatments included barley diet (96.24% of diet) and three other diets which malt was replacing with barley as 32.08, 64.16 and 96.24% (malt diet) were fed from 18-25 days of age. Experimental data were analyzed in a completely randomized design. Results of experiment indicated that digestible energy value and nutrient digestibility coefficients were significantly increased with replacing of malt with barley in experimental diets (p<0.01). Digestibility coefficients of protein, calcium and phosphorus in malt diet were significantly higher 16, 4.5 and 4% respectively, than barley diet (p<0.01). Digestible energy value determined for malt and barley using the regression analysis was 3213.34 and 2848.3 Kcal/Kg, respectively.